2014
DOI: 10.1080/19768354.2014.880372
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis byDioscorea nipponicaMakino extracts in human SH-SY5Y neuroblastoma cells via mitochondria-mediated pathway

Abstract: Dioscorea nipponica, a perennial herb growing in mountainous areas, has been used as a folk medicine for asthma, rheumatoid arthritis, bronchitis, and other disease in Korea, whereas the effect of this plant on cancer cells has not been clearly clarified. Cellular cytotoxicity was examined by cell viability assay and DNA fragmentation by DNA ladder assay. Activation of different protein expression was detected by western blot analyses. We first demonstrated that D. nipponica extract (DNE) reducing the SH-SY5Y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 51 publications
(54 reference statements)
0
13
0
Order By: Relevance
“…Furthermore, NF-κB inhibition with MG-132, proteasome inhibitor, along with idarubicin stimulated apoptosis of leukemic stem cells with significantly lesser that in normal hematopoietic stem cells (Guzman et al, 2002). Natural plant extracts from Melandrium firmum, Dioscorea nipponica Makino, and Saussurea lappa Clarke has been shown to have anti-proliferative and apoptotic effects in neuroblastoma cells (Rahman et al, 2013(Rahman et al, , 2014(Rahman et al, , 2015. Therefore, apoptosis signaling to CSC control in preclinical examination to propose the opportunity to eradicate cancers treatment.…”
Section: Controlling Cancer Stem Cells Through Apoptosis Signaling Pamentioning
confidence: 99%
“…Furthermore, NF-κB inhibition with MG-132, proteasome inhibitor, along with idarubicin stimulated apoptosis of leukemic stem cells with significantly lesser that in normal hematopoietic stem cells (Guzman et al, 2002). Natural plant extracts from Melandrium firmum, Dioscorea nipponica Makino, and Saussurea lappa Clarke has been shown to have anti-proliferative and apoptotic effects in neuroblastoma cells (Rahman et al, 2013(Rahman et al, , 2014(Rahman et al, , 2015. Therefore, apoptosis signaling to CSC control in preclinical examination to propose the opportunity to eradicate cancers treatment.…”
Section: Controlling Cancer Stem Cells Through Apoptosis Signaling Pamentioning
confidence: 99%
“…Therapeutics that decrease the activation of the mitochondrial fission proteins such as Drp1, pTau, and Aβ can rescue the neurons from the toxic effects of those agents and their interconnection. A diversity of phytochemicals available in numerous plant sources demonstrate various pharmacological properties, including neuroprotection [ 93 , 94 ], apoptosis induction [ 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 ], autophagy activation [ 79 , 103 , 104 , 105 ], antioxidant [ 106 ] and anti-inflammatory action [ 107 ], and DNA repair function [ 13 ]. Because of these capabilities, phytochemicals are progressively considered as favorable therapeutic candidates for AD therapy [ 10 ] ( Figure 4 ).…”
Section: Therapeutic Applications Of Phytochemicals In Mitochondrimentioning
confidence: 99%
“…Natural products and herbal medicine may be used for the management of neurodegeneration, cancer, and apoptosis [73][74][75][76][77][78][79][80] as well as autophagy inducer [81]. Recent studies revealed that active compounds in natural products exhibit curative effects against AD via a variety of mechanisms, including anti-cholinesterase activity, anti-apoptosis, and neuroprotective effects via antioxidation through targeting autophagy [82,83].…”
Section: Use Of Natural Compound To Modulate Autophagy In Admentioning
confidence: 99%